Analisis Penataan Reklame Berbasis Persepsi Masyarakat dan Pelaku Usaha (Studi : Jalan Kalimantan - Jalan Jawa Kabupaten Jember) - Safa Marella Pristrianti (Fakultas Teknik, 2026)
The growth of commercial activities in urban areas has driven increased use of billboards as promotional media, yet frequently generates visual pollution and incompatibility with urban aesthetic principles. This study aims to analyze the perceptions of the general public and business operators toward billboard arrangement and to formulate strategic recommendations along the Kalimantan – Jawa Road Corridor, Jember Regency. The Method employed is mixed methods, combining quantitative Importance-Performance Analysis (IPA) and qualitative SOAR (Strengths, Opportunities, Aspirations, Results) analysis. IPA results indicate that the main improvement priorities include controlling the number of billboards, ensuring placements do not obstruct pedestrian walkways, and simplifying the licensing process. The SOAR analysis produced three recommendations, namely proportional physical billboard arrangement, improvement of a transparent licensing system, and optimization of billboard function as a supportive urban element.
:: Finalisasi file repositori 4 Agustus 2026_Kurnadi
Keywords: Billboard; Urban Arrangement; Community Perception; Importance-Performance Analysis; SOAR